Identifying hot and cool spots in the city centre based on bicycle measurements: the case of Olomouc, Czech Republic - Lehnert, Michal; Kubeček, Josef; Geletič, Jan; Jurek, Martin; Frajer, Jindřich (Geographica Pannonica, 2018)
In this study we focus on a detailed analysis of air temperature in the city centre of Olomouc, using a bicycle for mobile measurements. We studied the spatial pattern of air temperature, analysed temperature differences between local climate zones (LCZs) and identified hot spots and cool spots in the city centre. The results point to a significant influence of microclimate and local climate on the field of temperature. In the daytime, hotspots occurred namely in LCZ 8 and E and in the well irradiated spaces within LCZ 2. Larger areas of scattered trees (LCZ B) in combination with watercourses created cool spots with a cooling potential for their surroundings. During night time, the warmest spots were detected mostly in LCZ 2 and the coolest spots in areas with low plants (LCZ D).